An Examination of Self-Reported Physical Activity and Physical Activity Self-Efficacy Among Children with Obesity: Findings from the Children’s Health and Activity Modification Program (C.H.A.M.P.) Pilot Study (Análisis de la actividad física autoreportad - Burke, Shauna M.; Vanderloo, Leigh M.; Gaston, Anca; Pearson, Erin S.; Tucker, Patricia (Retos, 2015)
Abstract. The increasing prevalence of childhood obesity is a global public health concern. Numerous experts have noted that comprehensive treatment methods are required to address this complex condition. The Children’s Health and Activity Modification Program (C.H.A.M.P.), a 4-week intervention delivered in a unique camp-based format, was developed for children with obesity and their families using a multidisciplinary approach. The purpose of the current study was to investigate the short- (i.e., 1-week post-intervention) and longer-term (i.e., 3-, 6-, and 12-months post-intervention) effects of C.H.A.M.P. on children’s self-reported: (a) task and barrier self-efficacy; and (b) home-based physical activity. A secondary purpose was to determine whether task and/or barrier self-efficacy served as predictors of self-reported home-based physical activity at any of these time points. The Physical Activity Questionnaire for Older Children (PAQ-C; Crocker, Bailey, Faulkner, Kowalski, & McGrath, 1997) was used to assess self-reported home-based physical activity and modified versions of the Self-Efficacy Scale and Barrier Efficacy Scale (McAuley & Mihalko, 1998) were administered to children to assess task and barrier self-efficacy, respectively. Forty participants (36 different children) completed Year 1 (n = 15; Mage = 10.6; 53% female) and/or Year 2 (n = 25; Mage = 10.6; 56% female) of the program. Results showed that participation in C.H.A.M.P. was associated with significant increases in task and barrier self-efficacy from pre- to post-intervention, after which mean values remained significantly higher than baseline at the 3- and 6-month follow-up assessments. No significant changes were observed from baseline to any of the post-intervention time points for home-based physical activity. Linear regression analysis revealed that task and barrier self-efficacy explained between 18% and 34% of the variance in self-reported home-based physical activity scores. While task self-efficacy contributed more towards the prediction of home-based activity at baseline, 1-week post-intervention, and 3-months post-intervention, barrier self-efficacy emerged as the predominant predictor at 6- and 12-months post-intervention. These results suggest that efficacious beliefs to be physically active and to overcome physical activity-related barriers may be important in the prediction of self-reported home-based physical activity in children with obesity. Taken together, the current findings also emphasize the importance of targeting self-efficacy as a first step towards increasing physical activity in this young population. Resumen. La creciente prevalencia de la obesidad infantil es un problema de salud pública mundial. Numerosos expertos han señalado que se requieren métodos de tratamiento integral para hacer frente a esta condición compleja. El programa de modificación de la salud y la actividad en niños (CHAMP), una intervención de 4 semanas diseñada en un formato único de tipo campamento, fue desarrollado para niños con obesidad y sus familias mediante un enfoque multidisciplinario. El objetivo del presente estudio fue investigar a corto plazo (es decir, 1 semana después de la intervención) y a largo plazo (es decir, 3, 6, y 12 meses después de la intervención) los efectos de CHAMP en la percepción subjetiva de los niños: (a) la autoeficacia en la tarea y en la barrera; y (b) la actividad física en el entorno familiar. Un objetivo secundario fue determinar si la autoeficacia en la tarea y/o barrera sirvió como predictores de la actividad física auto-reportada en el entorno familiar en cualquiera de estos puntos en el tiempo. El cuestionario de actividad física para niños mayores (PAQ-C; Crocker, Bailey, Faulkner, Kowalski, y McGrath, 1997) se utilizó para evaluar la actividad física auto-reportada en el contexto familiar y versiones modificadas de la escala de autoeficacia y la escala de eficacia de la barrera (McAuley y Mihalko, 1998) se administraron a los niños para evaluar la autoeficacia de tarea y relativa a las barreras, respectivamente. Cuarenta participantes (36 niños diferentes) completaron el año 1 (n = 15; Medad = 10,6; 53% chicas) y el año 2 (n = 25; Medad = 10,6; 56% chicas) del programa. Los resultados mostraron que la participación en C.H.A.M.P. se asoció con aumentos significativos en la autoeficacia de la tarea y la barrera en la pre y post-intervención, después de que los valores medios se mantuvieron significativamente más altos que en la línea base en las evaluaciones de seguimiento a los 3 y 6 meses. No se observaron cambios significativos desde el inicio hasta cualquiera de los puntos en el tiempo posteriores a la intervención para la actividad física en el entorno familiar. El análisis de regresión lineal reveló que la autoeficacia de tarea y de barrera explica entre el 18% y el 34% de la varianza en las puntuaciones de actividad física auto-reportada en el entorno familiar. Mientras la autoeficacia en la tarea contribuyó más a la predicción de la actividad física en el entorno familiar al inicio del estudio, la primera semana después de la intervención, y 3 meses después de la intervención, la autoeficacia en la barrera surgió como el factor de predicción predominante a los 6 y 12 meses después de la intervención. Estos resultados sugieren que las creencias eficaces para ser físicamente activo y para superar las barreras relacionadas con la actividad física son importantes en la predicción de la actividad física auto-reportada en el contexto familiar en niños con obesidad. En conjunto, los hallazgos actuales también hacen hincapié en la importancia de actuar sobre la autoeficacia como un primer paso hacia el aumento de la actividad física en esta población joven